NetAct: a computational platform to construct core transcription factor regulatory networks using gene activity. - Su, Kenong.; Katebi, Ataur.; Kohar, Vivek.; Clauss, Benjamin.; Gordin, Danya.; Qin, Zhaohui S; Karuturi, R. Krishna.; Li, Sheng.; Lu, Mingyang. (Tufts University. Tisch Library., 2023)
Keywords: Systems biology, Gene regulatory networks, Gene regulatory circuits, Cellular state transitions, Mathematical modeling, Transcriptional activity, Epithelial-mesenchymal transition, Macrophage polarization.; Springer Open.